Efficacy of Liderfeed® (eugenol) for chickens for fattening - Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; Kouba, Maryline; et al. (EFSA journal, 2017)
Liderfeed® is intended to be used as a zootechnical additive (functional group: other zootechnical additives) in feed of chickens for fattening to increase the performance. The additive contains eugenol as an active ingredient with some excipients and has not been authorised in the EU for use in food or feed. In 2015, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) adopted an opinion on the safety and efficacy of Liderfeed® as a zootechnical additive for chickens for fattening. In that opinion, the Panel could not conclude on the efficacy of the additive because only two out of the three efficacy studies considered showed a significant effect on the performance of chickens for fattening as a result of the supplementation with the additive. The Commission gave the applicant the possibility of submitting additional information to allow the FEEDAP Panel to complete its assessment. For this reason, additional data have been provided related to the efficacy of the additive for the target species and this new information is the subject of this opinion. The new efficacy study on chickens for fattening is the subject of this assessment; the results of this study indicate an improvement in performance parameters with the use of the additive at 100 mg/kg complete feed. Considering the results of the current study, along with the two efficacy studies already assessed in the previous FEEDAP Panel opinion of 2015, the Panel concludes that Liderfeed® at 100 mg/kg complete feed has the potential to improve the growth of chickens for fattening.